Cardiovascular risk according to abdominal circumference in Peruvians - Tarqui-Mamani, Carolina (2017)
Introduction: Excessive intra-abdominal fat is related to metabolic alterations that increase the risk of cardiovascular diseases. Objective: To describe the risk of cardiovascular disease according to abdominal circumference in Peruvians. Design: Cross-sectional study. Setting: National Institute of Health (NIH), Peru. Participants: Peruvians aged ≥12 years or older. Interventions: Probabilistic sampling, stratified, multistage. The sample included 1 191 conglomerates with 7 914 households distributed in Peru, in 2013-2014. 16 832 inhabitants ≥12 year old were evaluated. The cardiovascular risk was classified as low, high and very high. The NIH performed the AC assessment and the National Institute of Statistics and Informatics (NISI) calculated the sample and weights. Main outcome measures: Cardiovascular risk according to AC. Results: 50.1% presented low risk of cardiovascular disease, 22.8% high and 27.1% very high risk. The high risk for cardiovascular disease was more prevalent in women (42.5%), residing in the urban area (30.5%) (P <0.001), in Metropolitan Lima (32.6%) and in the coast (31.0%) (p <0.001). The high risk of cardiovascular disease was similar between sexes, being more frequent in the urban area (24.3%), Metropolitan Lima (25.1%) and the coast (24.2%). The high and very high risk of cardiovascular disease increased with age (p <0.001), except the high risk that decreased in the elderly. The risk of cardiovascular disease increased as poverty decreased (p <0.001). Conclusions: Half of the Peruvians twelve years and over presented high and very high risk of cardiovascular disease according to abdominal circumference.